PENINGKATAN MUTU GULA TUMBU MELALUI METODE SULFITASI DALAM LABORATORIUM - A Sutowo, Latief; Rizal, Syarief; Muhadiono, Muhadiono (Vocational School Diponegoro University, 2010)
A. Sutowo Latief, Rizal Syarief, Bambang Pramudya, Muhadiono, in this paper explain that the reseach was aimed to increase of brown sugarcane (gula tumbu) quality by sulphitation method in laboratory eksperimetal, supposed the result fulfils the first quality according to SNI 1-6237-2000 that is a minimal condition of safety food. The method based on factorial complete random plan thrice reduplications. Initially nira that filtered given lime tohor and heated 50-60oC up to achieve ph 9. The treatment: (1) make nira ph 7 and ph 8 with add sulphite acid, and (2) ripening temperature, that is 70,80,90, and 100oC. Nira that heated up to coagulate and it was poured into moulding and solidification to be brown sugarcane. The testing is done towards sugar quality, it was result with parameter: (1) water contain, (2) sucrose contain, (3) glucose contain, (4) rendemen, (5) colour, (6) taste, (6) smell, and (8) hardness of brown sugarcane that produced fulfil the first quality of SNI 1-6237-2000. The best treatment process heats nira in 100Â°C, either nira ph 7 and nira ph 8. Keywords: brown sugarcane, quality, sulfitation method.